Ethnography Of Communication Of Matt King In The Descendants Movie (2011) - Wulandari, Novitasari Wahyu Mukti; , Drs. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research aims at revealing and clarifying ethnography of communication of Matt King in The Descendants movie (2011) using SPEAKING grid. The type of research conducted by the researcher is descriptive research. The data and data source is dialogue of Matt King in The Decendants Movie. The method of collecting data employed by the writer is the document analysis and observation towards the movie. Based on the analyzed data the researcher finds : (l)Setting or Scene is at patient room, at staffroom, at schoolyard, at Mrs. Brab's house, at office, at Dr. John room, at the c1ub, at beach, at kitchen, at swimming pool, at yard, kay's house. (2) Participant is the sender and receiver. The sender is as informant, as family member, as husband, as father, and as friend. The receiver is as father, as husband, as family members, as friend and son-in-law. (3) End is giving information, getting information, asking apologize, giving praise, persuading. giving advice, commanding, showing, believing, and expressing his disappointment. (4) , :t sequence is in normal situation, regret situation, confused situation, intimate situation, wise situation, tense situation, sad situation, rush situation, slow situation, and disappointment situation. (5) Key consist of two parts, those are tone and manner. The tone of Matt King is flat, tense, worried, intimidate, emphatic, sad, and amazed. The manner is low intonation and high intonation. (6) Instruments are verbal communication and non-verbal communication. Verbal communication consists of formal style and non-formal style, non-verbal communication is hit Alex buttocks and throws the doll on the floor. (7) Genre of Matt King communication in The Descendant movie is dialogue and monologue.